Morphological changes in microvessels of guinea pigs lung in condition of sensitization and challenge with ovalbumin - Попко, Світлана Сергіївна; Popko, S. S. (Запорізький державний медичний університет, 2021)
The aim is to study the morphological changes in microvessels of guinea pigs lung in condition of sensitization and challenge with ovalbumin. Materials and methods. We have studied the lung of 48 guinea pigs, using histological and morphometric methods, under conditions of experimental ovalbumin-induced allergic inflammation, simulated by three times subcutaneous sensitization and subsequent 8-day intranasal inhalation of ovalbumin. To assess the structural and functional state of exchange and capacitive microvessels their inner diameter was determined. To assess the structural and functional state of medium (51 - 125 μm) and small (25 - 50 μm) arterioles their outer and inner diameters, the thickness of their tunica media and the Kernogan index were determined.
Keywords: тези